Changes in whey proteome with lactation stage and parity in dairy cows using a label-free proteomics approach. (February 2020) - Yang, Yongxin; Zheng, Nan; Zhao, Xiaowei; Yang, Jinhui; Zhang, Yangdong; Han, Rongwei; Zhao, Shengguo; Li, Songli; Wen, Fang; Wang, Jiaqi
Graphical abstract: Highlights: Changes in whey proteomes depending on the lactation stage and parity identified. Differences in whey proteome related to the lactation stage and parity revealed. Heparanase and syntenin may serve as biomarkers of specific lactation stages. Hemoglobin, β-lactoglobulin, and apolipoprotein E associated with the parity. Most of the altered proteins involved in response to stimulus and protein metabolic process. Abstract: Milk yield and several components of milk that are affected by physiological factors have been widely investigated. However, the effects of lactation stage and parity on bovine milk whey proteins have not been well elucidated. To aid in unraveling the proteome profile and exploring the protein biosynthesis of mammary glands, a label-free proteomic approach was used to characterize whey proteomes depending on the lactation stage and parity of dairy cows. The results of this study show that the abundances of several proteins, such as early lactation protein, syntenin, and heparanase, were associated with specific stages of the lactation cycle; this was evidenced by a principal component analysis. In addition, several proteins, such as hemoglobin subunits beta and alpha, β-lactoglobulin, CD320, and apolipoprotein E, corresponded to the parity of the dairy cows and were herein considered as useful biomarkers to distinguish different parities. Most of the differentially expressed proteins from specific lactation stages and parity milk groups were annotated in the response to stimulus and protein metabolic processes. The findings reveal that developmental changes in whey proteomes correspond to lactation stages and parities, which in turn provides new insight into the underlying implications of the production of specific proteins to meet the health benefits of offspring and host, and allow us to explore the mechanisms of protein biosynthesis in mammary glands associated with physiological changes in dairy cows.